Rebubbling of detached descemet membrane endothelial grafts at the slit lamp with 50% air fill after PI-less DMEK during COVID-19 era. Issue 3 (May 2021) - Franka, Mustafa; Mistry, Meera; Moustafa, Mohanad; Erikitola, Ore-oluwa; Lyall, Douglas
Purpose: To describe the effective use of only 50% air fill of the anterior chamber for rebubbling partially detached Descemet Membrane Endothelial Keratoplasty (DMEK) grafts at the slit lamp at a time of restricted operating theatre access during the COVID-19 pandemic. Methods: We present two cases of patients who underwent rebubbling of a partially detached DMEK grafts at the slit lamp following DMEK surgery without peripheral iridotomy. The rebubbling was performed with a 27-gauge needle attached to a 1ml syringe and the patients seated at the slit lamp. Air was injected into the anterior chamber until a 50% air fill was achieved. The patients were instructed to lie supine for 30 min in clinic and the remainder of the day at home. Results: We performed two rebubbling procedures at the slit lamp using the standard needle and syringe. Both cases achieved 50% air fills without any complications. At 3 days post-procedure the air bubble had resolved and the graft appeared attached centrally and at day 14 post-procedure the two patients had a clear and attached corneal graft with corrected visual acuity of 6/7.5 and 6/9, respectively. Conclusion: Rebubbling of detached DMEK grafts at the slit lamp with 50% air fill in the anterior chamber is a relatively simple and effective procedure. This provides an alternative approach for managing the complication of partially detached DMEK grafts in the era of COVID-19 with limited operating theatre access and avoids the risk of complications such as pupillary block in 'PI-less' DMEK.